N-Doped Graphene Quantum Dot Nanoparticle Synthesis of Optical Active Thermal Stable Polyurea Nanocomposites Using Polybutadiene Chain Modification - Zahra Rahmatpanah; Mir Mohammad Alavi Nikje; Maryam Dargahi (International Journal of Polymer Science)
Geminate thermal stability with optical characteristics is a moving forward achievement in the preparation of polybutadiene-based polyurea nanocomposites. In this regard, nitrogen-doped graphene quantum dots were synthesized from a one-pot hydrothermal reaction of citric acid with urea in an aqueous solution. An in situ polymerization approach was used for the synthesis of polyurea from the reaction of telechelic amine functionalized polybutadiene and toluene diisocyanate (TDI) in the presence of the DBTDL catalyst. Nanocomposites were prepared using 1–3 weight percent of graphene N-quantum dot nanoparticles in the polymer matrix. 1H-NMR and FT-IR spectroscopy techniques elaborated successful synthesis of primary polymer binder, polyurea and nanocomposites. Thermal degradation and characteristics were investigated using the TGA/DTG and DSC methods; lower degradation rates with progressed thermal stabilities as well as proportionate thermal characteristics with wider thermal service range were obtained especially in 3 wt% nanocomposite. Optical behavior information of samples was studied using UV-vis absorption and photoluminescence (PL) spectrometers. EDX, SEM, and AFM techniques confirmed successful nanoparticle and nanocomposite synthesis with improved morphologic and topographic properties.